Why do Countries enter into Preferential Agreements on Trade in Services? Assessing the Potential for Negotiated Regulatory Convergence in Asian Services Markets - Pierre Sauvé; Anirudh Shingal (Asian Development Bank (ADB), 2014)
More than half of the World Trade Organization (WTO)-notified services trade agreements (STAs) in effect since 2008 have involved at least one (South or Southeast) Asian trading partner. Drawing on Baier and Bergstrand's (2004) determinants of preferential trade agreements and using the World Bank's database on the restrictiveness of domestic services regimes (Borchert et.al. 2012), we examine the potential for negotiated regulatory convergence in Asian services markets. Our results suggest that countries within Asia that are more remote from the rest of the world and that have similar economic sizes, greater differences in relative factor endowments compared to the rest of the world, common legal origins, high levels of preexisting trade, and restrictive services regulations are more likely candidates for regulatory convergence. Our empirical model successfully predicts 10 of the 14 STAs negotiated during 2008–12 and 88 of the 89 dyads within Asia that lack an STA.
hdl:11540/1972
Keywords: F10; F13; F15; 330; PTAs; services; regulation; regulatory convergence; Asia